Pengaruh motivasi terhadap kepuasan dalam kalangan atlet sukan elektronik di universiti awam Melaka - Md Puad, Muhammad Adli Amirul (2024)
Electronic Sport is a video game competition, produced by a computer program and characterized by a competitive virtual space. The development of electronic sports has witnessed the emergence of a new industry in the form of commercial activities with high appeal. Studies on electronic sports involvement factors are still lacking in the Malaysian context. Accordingly, the objective of this study is to examine the influence between motivation and satisfaction of electronic sports athletes at Melaka Public University. The research methodology used a quantitative approach through survey research. The sampling used was purposive sampling given the limited number of athletes involved in electronic sports in line with criteria.. The study respondents consisted of 120 electronic sports athletes from public universities in Melaka who participated in electronic sports tournaments. This study was held at public universities in Malacca. The design of this study was in the form of impact study. Data was distributed to respondents who were involved in electronic sports held from year 2020 to 2022. Data were analyzed by using the Statistical Package for the Social Sciences (SPSS) version 24.0. Descriptive analysis, Pearson correlation and Multiple Linear regression were used to study the relationship between motivation and satisfaction among electronic sports athletes at public universities in Malacca. The results of the study showed that there were only four motivational factors namely competitive motivation, diversion, entertainment, and social that showed a significant effect on satisfaction among the electronic sports athletes of the public university in Malacca. This study is useful for the reference of electronic sports researchers in the field of sports science, the University Sports Council and the National Sports Council for the development of athletes as well as supporting the development of the Malaysian sports industry and also contributing to the development of electronic sports policy. In addition, it triggers public awareness regarding the nature of the responsibility of electronic sports to the community regarding the advantages that outweigh the disadvantages.